Salvage external beam radiotherapy after HIFU failure in localized prostate cancer: A single institution experience - Di Lalla, Vanessa; Elakshar, Sara; Anidjar, Maurice; Tolba, Marwan; Hassan, Toufic; Bahoric, Boris; McPherson, Victor; Probst, Stephan; Niazi, Tamim (Frontiers in Oncology, 2022)
Purpose/Objectives: High-intensity focused ultrasound (HIFU) remains investigational as primary treatment for localized prostate cancer but is sometimes offered to select patients. At HIFU failure, data guiding salvage treatment is limited to small retrospective series with short follow-up. We evaluated our institutional experience using salvage radiation therapy (SRT) after HIFU failure. Materials/Methods: We conducted a retrospective analysis of patients with local failure post-HIFU who received salvage image-guided external beam radiation therapy (EBRT) delivered via intensity-modulated radiotherapy (IMRT). Our primary endpoint was biochemical failure-free survival (bFFS) defined as prostate-specific antigen (PSA) nadir + 2 ng/mL. Secondary endpoints included metastasis-free survival (MFS) and overall survival (OS). Endpoints were evaluated using Kaplan-Meier analysis. Results: From 2013 to 2018, 12 out of 96 patients treated with primary HIFU received SRT via conventional or moderate hypofractionation. Median time from HIFU to SRT was 13.5 months. Seven patients had stage migration to high-risk disease at the time of SRT. Mean PSA prior to SRT was 8.2ug/L and mean nadir post-SRT was 1.2ug/L. Acute International Prostate Symptom Score (IPSS) as well as International Index of Erectile Dysfunction (IIEF) scores were similar to baseline (p = 0.5 and 0.1, respectively). Late toxicities were comparable to those reported after primary EBRT for localized prostate cancer. At a median follow-up of 46 months, the OS was 100%. The 5-year bFFS and MFS were both 83.3%. Conclusions: To our knowledge, we report one of the largest series on contemporary SRT post HIFU failure. We show that SRT is feasible, effective and carries no additional acute or delayed toxicity.